2017
DOI: 10.1146/annurev-physiol-021115-104948
|View full text |Cite
|
Sign up to set email alerts
|

Three Pillars for the Neural Control of Appetite

Abstract: The neural control of appetite is important for understanding motivated behavior as well as the present rising prevalence of obesity. Over the past several years, new tools for cell type-specific neuron activity monitoring and perturbation have enabled increasingly detailed analyses of the mechanisms underlying appetite-control systems. Three major neural circuits strongly and acutely influence appetite but with notably different characteristics. Although these circuits interact, they have distinct properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
194
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(210 citation statements)
references
References 150 publications
4
194
0
1
Order By: Relevance
“…In this way, the magnitude of the rapid drop in AgRP neuron activity following cues predicting upcoming food consumption may reflect the expected reduction in energy deficit once this immediately available food is consumed, digested, and absorbed. Consistent with this view, when food consumption instead consists of several small meals, each anticipated to be less than that required to restore energy homeostasis (Figure 10B,C), AgRP firing undergoes successive drops to lower firing levels (Betley et al, 2015; Chen et al, 2015; Livneh et al, 2017; Sternson and Eiselt, 2017). Consumption of even smaller quantities of food, each replenishing only a tiny fraction of the total energy deficit (as is the case during many operant behavioral tasks) results in AgRP activity remaining elevated (Figure 10C), with only slight drops following food detection (Livneh et al, 2017).…”
Section: Section 3: Hypothalamic Regulation Of Hunger/satietymentioning
confidence: 58%
See 3 more Smart Citations
“…In this way, the magnitude of the rapid drop in AgRP neuron activity following cues predicting upcoming food consumption may reflect the expected reduction in energy deficit once this immediately available food is consumed, digested, and absorbed. Consistent with this view, when food consumption instead consists of several small meals, each anticipated to be less than that required to restore energy homeostasis (Figure 10B,C), AgRP firing undergoes successive drops to lower firing levels (Betley et al, 2015; Chen et al, 2015; Livneh et al, 2017; Sternson and Eiselt, 2017). Consumption of even smaller quantities of food, each replenishing only a tiny fraction of the total energy deficit (as is the case during many operant behavioral tasks) results in AgRP activity remaining elevated (Figure 10C), with only slight drops following food detection (Livneh et al, 2017).…”
Section: Section 3: Hypothalamic Regulation Of Hunger/satietymentioning
confidence: 58%
“…A complementary role for rapid changes in AgRP neuron activity was proposed by Sternson and colleagues (Betley et al, 2015; Sternson and Eiselt, 2017). These authors found that AgRP neuron stimulation was mildly aversive, and suggest that the drop in AgRP activity may provide rapid relief from this aversive state and act as a teaching signal to reinforce learning of cues predicting food (but see (Chen et al, 2016) for an alternative interpretation).…”
Section: Section 3: Hypothalamic Regulation Of Hunger/satietymentioning
confidence: 91%
See 2 more Smart Citations
“…These events are not detected by current pulse analysis algorithms, and indicate the need for the further development of LH pulse analysis methodologies. In terms of ARN function, it is intriguing to find a 10-min neuronal oscillator embedded among ARN neural circuitries subserving longer-term functions such as feeding initiation (29). With evidence for kisspeptin inputs into these feeding circuits and others (30), it will be interesting to examine the impact of this fast oscillator on other ARN outputs in future studies.…”
Section: Discussionmentioning
confidence: 99%